Financial variables as predictors of real growth vulnerability - Lucrezia Reichlin; Giovanni Ricco; Thomas Hasenzagl (Deutsche Bundesbank, 2020)
We evaluate the role of financial conditions as predictors of macroeconomic risk first in the quantile regression framework of Adrian et al. (2019b), which allows for non-linearities, and then in a novel linear semi-structural model as proposed by Hasenzagl et al. (2018). We distinguish between price variables such as credit spreads and stock variables such as leverage. We find that (i) although the spreads correlate with the left tail of the conditional distribution of GDP growth, they provide limited advanced information on growth vulnerability; (ii) nonfinancial leverage provides a leading signal for the left quantile of the GDP growth distribution in the 2008 recession; (iii) measures of excess leverage conceptually similar to the Basel gap, but cleaned from business cycle dynamics via the lenses of the semi-structural model, point to two peaks of accumulation of risks - the eighties and the first eight years of the new millennium, with an unstable relationship with business cycle chronology.
Keywords: E32; E44; C32; C53; 330; financial cycle; business cycle; credit; financial crises; downside risk; entropy; quantile regressions